Personal care workers in Australian aged care: retention and turnover intentions. (13th November 2013) - Radford, Katrina; Shacklock, Kate; Bradley, Graham
<x xml:space="preserve">Abstract</x> Aim This study examined factors influencing personal care workers' intentions to stay or leave Australian aged care employment – especially for older workers. Background Retention of personal care workers is particularly important in aged care as they provide the majority of the direct care via community aged care or long‐term aged care environments. However, there is limited research on what drives their turnover and retention. Method A survey was conducted during 2012 collecting 206 responses from workers within community and long‐term aged care in four organisations in Australia. Result Perceived supervisor support, on‐the‐job embeddedness and area of employment were identified as predictors of both intention to stay and to leave, although the relationship strength differed. Community care workers were more likely to stay and reported more supervisor support than long‐term care workers. Unexpectedly, age and health status were not predictors of staying or leaving. Conclusion While there are similarities between retention and turnover motivators, there are also differences. Within a global context of health worker shortages, such new knowledge is keenly sought to enhance organisational effectiveness and sustain the provision of quality aged care. Implications for nursing management Retention strategies for older workers should involve increasing supervisor support, and seeking to embed workers more fully within their organisation.